ANTARA STRUKTURAL DAN PRAGMATIK DALAM KALIMAT YANG BERINFORMASI GANDA - mintoyo, Her (HUMANIKA, 2013)
ABSTRACT Linguistics is divided into two areas, namely microlinguistic and makrolinguistic. Microlinguistic area include structurally theoretical study, while makrolinguistic area include interdisciplinary and applied. One of the interdisciplinary domain is study of pragmatics. Pragmatics deals with the interpretation of a phrase made ​​to follow certain syntactical rules, and how to interpret these expressions depend on the particular circumstances in the context of the use of the phrase. Pragmatics is the study of the relationship between language and context of gramatically or codified in language structure. Accordingly, the study of pragmatics as macrolinguistic is a supporting for microlinguistic. Keywords: structural, pragmatic, contex